Advanced Targeted Nanomedicine A Communication Engineering Solution - Chude-Okonkwo, Uche; Malekian, Reza; Maharaj, BT (Nanomedicine and Nanotoxicology,, 2019)
This book presents medical challenges as communication engineering problems. It offers the reader the interesting perspective of exploring and understanding disease pathology from the point of view of communication engineers. Therefore, diseases and their treatments can be addressed using conventional communication paradigms, approaches, tools and devices; thereby ushering in the interdisciplinary research platform termed advanced targeted nanomedicine. The rudimentary framework for advanced targeted nanomedicine is presented and expatiated across the seven chapters of this book.